Inactivation of Crk SH3 domain‐binding guanine nucleotide‐releasing factor (C3G) in cervical squamous cell carcinoma. Issue 2 (1st March 2006) - Okino, K.; Nagai, H.; Nakayama, H.; Doi, D.; Yoneyama, K.; Konishi, H.; Takeshita, T.
Abstract : C3G, a Crk SH3 domain-binding guanine nucleotide-releasing factor functions as a guanine nucleotide exchange factor for Rap1. It is activated via the Crk adaptor protein and plays an important role in transducing signals from receptors on the cell surface to the nucleus via the Ras/Raf/MAPK signal transduction pathway. However, since the experimental data result in pleiotropic effects in the cascade manner, its precise function remains unclear. Here we examined the C3G expression in cervical squamous cell carcinomas and found a marked decrease in the expression of C3G in a high incidence of said samples. In addition, we also demonstrated frequent hypermethylation of C3G, which resulted in an inactivation mechanism of the gene. Clinical and pathologic data failed to show any relationship between the human papillomavirus infection and the down-regulation of C3G . These results indicate that inactivation of C3G by de novo methylation plays an important role in the development of cervical squamous cell carcinoma.